What are the probable predictors of urinary incontinence during pregnancy? - Demircan, Nejat; Özmen, Ülkü; Köktürk, Fürüzan; Küçük, Hamdi; Ata, Şevket; Harma, Müge; Arıkan, İnan İlker (PeerJ, 2016)
Objectives. The frequency, predisposing factors and impact of urinary incontinence (UI) on quality of life (QoL) during pregnancy were investigated. Materials and Method. A preliminary cross-sectional survey was studied among pregnant women between January and July of 2014. A total of 132 pregnant women were recruited using a questionnaire form for sociodemographic features, the Turkish version of the International Consultation on Incontinence-Short Form (ICIQ-SF), for the characteristics of UI and Wagner’s Quality of Life scale to assess impact on QoL. p < 0.05 was set significant. Results.Urinary incontinence was present in 56 out of 132 pregnant women (42.4%, UI-present group): mean age, 26.7 ± 5.4y(p = 0.780); median height, 160 cm (min–max: 153–176, p = 0.037); median BMI, 28.7 kg/m2(min–max: 22.4–50.0, p = 0.881); urine leakage occurred per week once (n = 18, 32.1%), twice or thrice (n = 8, 14.3%); per day few times (n = 14, 25%), once (n = 5, 8.9%) and always (n = 8, 14.3%) with mainly a small amount of urine leakage (n = 33, 58.9%) or a moderate (n = 4, 7.1%). There were statistically significant relationships between QoL scores and frequency of UI (p = 0.002) or amount of leakage (p = 0.002). Impact on QoL scores ranged from mild (n = 33, 58.9%), moderate (n = 4, 7.1%) to severe (n = 4, 7.1%) levels in daily life. UI impacted the daily life activities of women by making them less likely to undertake activities outside their homes (23.2%), by affecting their working performance and friendships (8.9%), their daily home activities (7.1%), their general health status (12.5%), their sexual relations (12.5%), by making them more nervous or anxious (10.7%) and by the need to wear pads or protectors (25%). ANOVA, Tukey, and Tamhane tests as the minimal important difference model yielded significant relevance between statistical analyses and clinical outcomes by using standard deviations (p = 0.001, 0.001 and 0.005 respectively). The following features favored the occurence of UI: Age (OR = 0.845, 95% CI [0.268–2.669]), being a housewife (OR = 1.800, 95% CI [0.850–3.810]), anemia (OR = 0.939, 95% CI [0.464–1.901]), parity (OR = 0.519, 95% CI [0.325–0.829]), miscarriage (OR = 1.219, 95% CI [0.588–2.825]) and living in rural areas (OR = 1.800, 95% CI [0.887–3.653]). Height (p = 0, 037), educational status (0.016), miscarriage (0.002), parity (0.006) and place of living (0.020) were significant factors. Conclusions.Many pregnant women are suffering from UI, which warrants a significant public health consideration in the region. Age, height, being a housewife or graduation level higher than primary school, living in rural, parity, miscarriage, and anemia were the factors in favor of the onset of UI. The authors plan a health promotion program in the region according to the results in order to provide information to health caregivers, especially family physicians, and to educate women about the predictors of UI and pelvic floor exercises for primary prevention and secondary relief of UI during and after pregnancy and provide some hygienic supplies to the poor in this aspect.
Keywords: Life quality; Miscarriage; Parity; Pregnancy; Urinary incontinence; Women’s health; Anemia; Rural vs. urban; Housewife; Body mass index